Induced Currents on a Moving and Vibrating Perfect Plane Under the Illumination of Electromagnetic Pulse: One-Dimensional Simulation using Characteristic-Based Algorithm - Ho, Mingtsu (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper provides one-dimensional simulation results of the induced currents on constantly moving and vibrating perfect conductors under the normal illumination of plane Gaussian electromagnetic pulses. The characteristic-based algorithm is employed for the solutions of time-dependent Maxwell curl equations. In the numerical model, the size of the computational cell adjacent to the moving boundary, and its corresponding numerical time step become timedependent since the boundary is not stationary. By comparing the computational results with the theoretical Doppler shift values, we show that the present method successfully predicts the induced currents on the perfect conductor surface. The computed electric and magnetic field intensities and induced currents are demonstrated as well.